Activity report of the 52nd Japanese Antarctic Research Expedition (JARE-52) wintering party in 2011-2012 - Hitomi Miyamoto; Masaki Tsutsumi (National Institute of Polar Research, 2014)
The outline of the activities of the 52nd Japanese Antarctic Research Expedition (JARE-52) wintering party is reported. JARE-52 wintering party conducted the first year research and logistical program in the eighth six-year plan of Japanese Antarctic Program after taking over management of Syowa Station from JARE-51 wintering party on February 1, 2011. Extremely deep snow was observed throughout the year. JARE-52 started the comprehensive observation of Antarctic atmosphere as one of the prioritized studies of the eighth six-year plan “The study of global climate change through the observation of the middle and upper atmosphere over the Antarctic”. JARE-52 developed runways on sea ice off the coast of Syowa Station for the Dronning Maud Land Air Network (DROMLAN). As outreach activities, remote class programs for children and students were performed 19 times through the satellite TV conference system from Syowa Station. Because the icebreaker Shirase could not reach the coast of Syowa Station for the first time in 18 years, long-distance transportation on sea ice was carried out from January 24 to February 10, 2012.